1992
DOI: 10.1177/026839629200700202
|View full text |Cite
|
Sign up to set email alerts
|

The Automation of Accounting Practice

Abstract: This article examines the use of computer technology by the UK accounting profession. The first part of the paper examines the nature of the accounting environment and identifies a number of reasons why accounting automation should be an issue of general concern. A particular accounting task, auditing, is examined in detail to illustrate some of the factors affecting accounting automation. The second part of the paper reports the findings of an empirical examination of computerization amongst a number of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 2 publications
1
15
0
Order By: Relevance
“…The main difference between this study's finding and those of the last two is that Banker et al (2002) did not distinguish between professional and clerical/administrative labour in its assertion while Manson et al (1997) only concentrated on professional staff. The finding totally agrees with the work of Wilson and Sangster (1992) who suggested that the effect of ICT on accounting has been to increase the overall level of professional employment but marginally decrease the overall level of clerical employment.…”
Section: Rq1c: Does Audit Automation Lead To Power Shift In Audit Firsupporting
confidence: 91%
“…The main difference between this study's finding and those of the last two is that Banker et al (2002) did not distinguish between professional and clerical/administrative labour in its assertion while Manson et al (1997) only concentrated on professional staff. The finding totally agrees with the work of Wilson and Sangster (1992) who suggested that the effect of ICT on accounting has been to increase the overall level of professional employment but marginally decrease the overall level of clerical employment.…”
Section: Rq1c: Does Audit Automation Lead To Power Shift In Audit Firsupporting
confidence: 91%
“…While widely neglected by prior research, we consider automation to be particularly relevant in MA. Routine tasks, such as bookkeeping or invoicing, can be easily automated, enabling management accountants to focus more on cognitively complex tasks (Scapens and Jazayeri 2003;Wilson and Sangster 1992). Thus, we propose to incorporate automation as an indicator of IS quality.…”
Section: Discussionmentioning
confidence: 99%
“…6 The respondents are asked to indicate the number of firms (i.e., subsidiaries, joint ventures) consolidated in MA within the following categories: 1 consolidated firm, 2-10 consolidated firms, 11-30 consolidated firms, 31-100 consolidated firms, and more than 100 consolidated firms. 7 Second, following Thong and Yap (1995), firm size may cause differences in the extent of IT adoption because it affects company's IT investments, professional expertise, complexity, and resistance to change (Raymond 1990;Wilson and Sangster 1992). We control for firm size (SIZE), which we operationalize in terms of annual revenue at the corporate level.…”
Section: Control Variablesmentioning
confidence: 99%
“…There are different reasons why accountants should accept and apply modern digital solutions. Factors that can have a significant impact and be a motivation for technological change according to study conducted by Wilson et al (1992) among the UK accounting profession are as follows: need to meet prescribed deadline for accounting tasks and the importance to provide better and timely information for different users. Furthermore, by using technology the quality and relevance of the accounting information will be improved (Al-Htaybat et al, 2017), the period needed for preparation will be shortened and information will be available in real time without delay.…”
Section: Digitalization and Accounting Professionmentioning
confidence: 99%